A highly efficient catalytic α-alkylation of unactivated amides using primary alcohols. Issue 26 (29th June 2016) - Yao, Wubing; Ma, Xiaochen; Guo, Le; Jia, Xiangqing; Hu, Aiguo; Huang, Zheng
Graphical abstract: Highlights: Unprecedented high activity for α-alkylations of unactivated amides. Mild reaction conditions and low catalyst loadings. Broad substrate scope with respect to acetamides and alcohols. Wide functional group compatibility. Abstract: The α-alkylation of unactivated amides with alcohols is described. Using a NCP-type pincer Ir complex as the precatalyst and KO t Bu as the base, the reactions of secondary or tertiary acetamides with benzyl or nonbenzyl primary alcohols occur at 80 °C, furnishing the alkylation products in good yields. This method represents a practical and green means of α-alkylation of amides in a relatively mild, efficient, and selective manner with low catalyst loadings (0.5 mol %).